2010
DOI: 10.1103/physreva.82.022326
|View full text |Cite
|
Sign up to set email alerts
|

Using postmeasurement information in state discrimination

Abstract: We consider a special form of state discrimination in which after the measurement we are given additional information that may help us identify the state. This task plays a central role in the analysis of quantum cryptographic protocols in the noisy-storage model, where the identity of the state corresponds to a certain bit string, and the additional information is typically a choice of encoding that is initially unknown to the cheating party. We first provide simple optimality conditions for measurements for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 29 publications
(55 reference statements)
1
38
0
Order By: Relevance
“…A typical instance of this problem is called state discrimination with post-measurement information [18,19]. The ensemble E = {p a , a } a∈I can be partitioned into nonempty disjoint ensembles E x = {p a , a } a∈Ix , where…”
mentioning
confidence: 99%
“…A typical instance of this problem is called state discrimination with post-measurement information [18,19]. The ensemble E = {p a , a } a∈I can be partitioned into nonempty disjoint ensembles E x = {p a , a } a∈Ix , where…”
mentioning
confidence: 99%
“…A particular instance of the scheme introduced in this section is the discrimination task with pre-and postmeasurement information described and studied in [12,35,36,37]. In the latter task, Bob is asked to retrieve Alice's label z ∈ X 1 ∪ X 2 by simply performing a measurement N on the received state a z , without making any processing of a z before that.…”
Section: Channel Incompatibility Witnesses As a State Discrimination mentioning
confidence: 99%
“…In this task, Alice encodes classical information in quantum states and Bob then performs a measurement to guess the correct state, but Alice announces some partial information on her encoding before Bob must make his guess. This task was further studied in [5], and it was suggested that the usefulness of post-measurement information distinguishes the quantum from the classical world. In this work we reveal a link between the task of state discrimination with post-measurement information and the incompatibility of quantum measurements.…”
Section: Introductionmentioning
confidence: 99%